2014
DOI: 10.1159/000365393
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutations Are Not Observed by Exome Sequencing of Lymphocyte DNA from Monozygotic Twins Discordant for Congenital Hypothyroidism due to Thyroid Dysgenesis

Abstract: Background/Aims: Congenital primary hypothyroidism (CH) is a rare pediatric disorder estimated to occur in about 1:2,500 live births. Approximately half of these cases entail ectopic thyroid tissue, which is believed to result from a migration defect during embryogenesis. Approximately 3% of CH cases are explained by mutation(s) in known genes, most of which are transcription factors implicated in the embryology of the thyroid gland. Surprisingly, monozygotic (MZ) twins are usually discordant for CH due to thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
3
13
0
2
Order By: Relevance
“…In the present study, no genetic differences were detected in MZ twins discordant for cryptorchidism. The results coincided with the findings of earlier similar studies, in which no genetic discordances were found in MZ twins discordant for several disorders, including renal agenesis (Jin et al, 2014), cataract (Wei et al, 2015), VACTERL association (Solomon et al, 2013), hypothyroidism (Magne et al, 2015), heart defects, and diaphragmatic hernia (Zhang et al, 2016). Our findings provide additional evidence that genetic mutations are not a common cause for phenotypic discordance among MZ twins.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, no genetic differences were detected in MZ twins discordant for cryptorchidism. The results coincided with the findings of earlier similar studies, in which no genetic discordances were found in MZ twins discordant for several disorders, including renal agenesis (Jin et al, 2014), cataract (Wei et al, 2015), VACTERL association (Solomon et al, 2013), hypothyroidism (Magne et al, 2015), heart defects, and diaphragmatic hernia (Zhang et al, 2016). Our findings provide additional evidence that genetic mutations are not a common cause for phenotypic discordance among MZ twins.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, a recent study showed no peculiar thyroid ectopy‐specific methylation signature after performing a genome‐wide DNA methylation analysis . In addition, somatic mutations were not detected in TD‐discordant monozygotic twins by exome sequencing …”
Section: Discussionmentioning
confidence: 98%
“…77 In addition, somatic mutations were not detected in TD-discordant monozygotic twins by exome sequencing. 78 Autosomal monoallelic expression (AME) defines unusual autosomal genes with random choice between the maternal and paternal expressed allele. 79 AME can be classified into two groups: (a) fixed, in which the allele-specific expression of a precursor cell is conserved in descendant cells; and (b) dynamic, which is not transmitted along mitosis and, therefore, can be investigated only at the single cell level.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the only study to investigate this, the gene expression pattern was different in ectopic thyroid, but this was not attributable to significant somatic methylation gene expression profile differences (85). Additionally, frequent somatic mutations were not identified in lymphocyte DNA from monozygotic twins discordant for TD (86) although somatic mosaicism for a PAX8 mutation has been reported (87). Autosomal monoallelic expression has been reported for some genes in both ectopic and eutopic thyroid (88); however, monoallelic expression of a mutant allele has only been reported for TPO in association with dyshormonogeneic CH (89).…”
Section: Alternative Genetic Aetiologies In Td and Dyshormonogenetic Chmentioning
confidence: 89%